The Proton-Boron Reaction Increases the Radiobiological Effectiveness of Clinical Low- and High-Energy Proton Beams: Novel Experimental Evidence and Perspectives - Bláha, Pavel; Feoli, Chiara; Agosteo, Stefano; Calvaruso, Marco; Cammarata, Francesco Paolo; Catalano, Roberto; Ciocca, Mario; Cirrone, Giuseppe Antonio Pablo; Conte, Valeria; Cuttone, Giacomo; Facoetti, Angelica; Forte, Giusi Irma; et al. (Frontiers in Oncology, 2021)
Protontherapy is a rapidly expanding radiotherapy modality where accelerated proton beams are used to precisely deliver the dose to the tumour target but is generally considered ineffective against radioresistant tumours. Proton-Boron Capture Therapy (PBCT) is a novel approach aimed at enhancing proton biological effectiveness. PBCT exploits a nuclear fusion reaction between low-energy protons and 11B atoms, i.e. p+11B→ 3 alpha particles (p-B), which is supposed to produce highly-DNA damaging -particles exclusively across the tumour-conformed Spread-Out Bragg Peak (SOBP), without harming healthy tissues in the beam entrance channel. To confirm previous work on PBCT, here we report new in-vitro data obtained at the 62-MeV ocular melanoma-dedicated proton beamline of the INFN-Laboratori Nazionali del Sud (LNS), Catania, Italy. For the first time, we also tested PBCT at the 250-MeV proton beamline used for deep-seated cancers at the Centro Nazionale di Adroterapia Oncologica (CNAO), Pavia, Italy. We used Sodium Mercaptododecaborate (BSH) as 11B carrier, DU145 prostate cancer cells to assess cell killing and non-cancer epithelial breast MCF-10A cells for quantifying chromosome aberrations (CAs) by FISH painting and DNA repair pathway protein expression by western blotting. Cells were exposed at various depths along the two clinical SOBPs. Compared to exposure in the absence of boron, proton irradiation in the presence of BSH significantly reduced DU145 clonogenic survival and increased both frequency and complexity of CAs in MCF-10A cells at the mid- and distal SOBP positions, but not at the beam entrance. BSH-mediated enhancement of DNA damage response was also found at mid-SOBP. These results corroborate PBCT as a strategy to render protontherapy amenable towards radiotherapy-resilient tumour. If coupled with emerging proton FLASH radiotherapy modalities, PBCT could thus widen the protontherapy therapeutic index.